Aligning Employee Competency in Achieving Corporate Goals to Compete with Another Agencies - Putri Afrili, Amanda; Ros Bangun, Yuni (The Indonesian Journal of Business Administration, 2017)
Abstract - This thesis research is aim to analyze the current situation both internally and externally of PT Komunikasi Maya Bestari (Communicaption) and preparing the employee competencies in achieving corporate goals to compete with another agency. Communicaption as a new start-up agency that has been established since 2011 nowadays need to compete in this rapid competition among digital agency in Indonesia. Indonesia, as the 29th position among all countries and 6th position in South East Asia or internet penetration consider that digital industry now raise significantly. Around 51% of Indonesia population are active using internet and Indonesia get 3rd position of social media growth rank among all countries (Wearesocial.com, 2017). The internet usage also made an impact for corporate to promote their brand through digital tools such as website, social media, mobile-apps and so on. This thesis is focus on finding various things to be improved to preparing and aligning employee competencies with corporate goals. Using various method such as workload analysis, competency analysis, IFE-EFE matrix, CPM matrix and SWOT analysis, researcher find out that Communicaption has some obstacle in their internal aspects, however they have various strengths in running their business. Researcher give various suggestion and activity recommendation to support its management in aligning employee competencies to achieve corporate goals. Keywords: employee competency, corporate goals, digital agency, industry competency